Assessment of concussion knowledge, attitudes, and behaviors among adolescent female club soccer athletes - Davidson, B.; Anglim, M.; Williams, R. M. (International Journal of Athletic Therapy & Training, 2023)
Concussion education for athletes is essential for informed decision making to aid recovery. Education about concussion symptoms, treatment, and protocols can improve symptom recognition, reporting behaviors, protocol compliance, and overall health outcomes. This pilot study aimed to understand current concussion knowledge, attitudes, and beliefs among female club soccer players aged 12-18 years. Findings identified gaps in concussion education and knowledge among these athletes. Continued concussion education efforts are needed to increase concussion knowledge and players` confidence, focusing on creative education practices.